Revealing the Islamic Heritage of the Nusantara: Philological Study of the Manuscript Hizbul Aman Min Satowatil Zaman by Muhammad Amin Bin Muhammad Hasan Al-Banjary - Safitri, Entin; Aisyah, Aisyah; Rohavik, Opik; Erlina, Erlina; Achmad, Achmad (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study examines the religious text manuscript Hizbul Aman Min Satowatil Zaman by Muhammad Amin bin Muhammad Hasan al-Banjari. The manuscript is part of the intellectual heritage of Nusantara Islamic literature, rich with prayers and dhikr, reflecting spiritual values and local culture. The method employed is descriptive philology with a contextual approach to uncover the cultural meanings within each text. The main objective of this research is to interpret the content of the manuscript as a reflection of the religious traditions of the Muslim community in Nusantara. The urgency of this study lies in the preservation of intellectual and spiritual heritage, contributing to a deeper understanding of local Islam. The research problem addresses how the texts in this manuscript articulate the relationship between faith and local culture. The research questions include the meaning of each section of the text within the context of Malay Islamic culture and its relevance to the religious practices of the community. The proposed solution is to accurately translate the text while providing cultural interpretations embedded in each page. The findings indicate that the manuscript is an integral part of traditional practices such as tahlilan, shalawat, and the commemoration of the Prophet's birthday (Maulid Nabi). This finding reinforces that this classic manuscript is integral to the Nusantara Islamic tradition and has relevance in understanding local Islamic identity.